ANALISIS PENGARUH CORPORATE GOVERNANCE DAN MANAJEMEN LABA TERHADAP LIKUIDITAS - Cita Ratna Setyamurti; Dul Muid (Diponegoro Journal of Accounting, 2015)
The aims of this study is to examine influence of corporate governance mechanism and earnings  management  on  liquidity.  Independent  variables  used  in  this  study  is  corporate governance and earnings quality. Corporate governance was measured by proportion independent commisioner, composition of audit committee, meetings of audit committee and institutional. Earnings quality was measured by earnings management. Dependent variable in this study is stock liquidity, it was measured by trading volume. Population in this study is non-financial companies listing in LQ 45 index in 2011-2013. Samples are obtained by purposive sampling method with a total of 90 companies in three years observation. Result of this research indicates is composition of audit committee and earnings management had a significant positive effect to trading volume. Institusional ownership had a significant negative effect to trading volume. Meanwhile, proportion of independent commisioner and meetings of audit committee had not significant effect to trading volume.